ISSUES OF MODELING THE TARIFF FOR SERVICES IN MOTOR TRANSPORT ON THE BASIS OF CORRELATION-REGRESSION ANALYSI - Matkarim?v K?m?liddin Jurabayevich (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article describes the state of freight and passenger transport in the Republic of Uzbekistan, the role of road transport in the transport system, the state of development of the road network, the existing problems based on the results of theoretical and practical research of the author. Based on the use of foreign experience, proposals and recommendations for the development of the road complex have been developed with the widespread use of grouping, comparison, economic and statistical methods. This research paper also describes the research conducted to determine the supply and demand for services of enterprises of the road complex, modeling the cost and cost of road services, model and algorithm of parking in the construction of roads, forecasting the cost of transport services.